The effectiveness of blended learning using the Madrasati platform in developing critical thinking skills and developing attitudes towards it among secondary school students in the Kingdom of Saudi Arabia - Al-Raddadi, Fahd Ayed (Journal of Curriculum and Teaching Methodology, 2025)
The current study aimed to measure the effectiveness of blended learning using the Madrasati platform in developing critical thinking skills and developing the attitude towards it among secondary school students. Critical thinking, and a measure of the trend towards blended learning. The study sample consisted of all (115) students in the first year of secondary school from Abi Saeed Secondary School affiliated to the General Administration of Education in Al-Madinah Al-Munawwarah region. The study sample was chosen randomly. The results showed that there were statistically significant differences at the level of significance (α = 0.05) between the average performance of the study sample in the critical thinking skills test (knowledge of assumptions, interpretation, evaluation of discussions, deduction, conclusion) sporadic (each skill separately) and combined (as a whole). in favor of telemetry, The results also showed that there were statistically significant differences at the significance level (α = 0.05) between the mean trends of the study sample in the measure of attitude towards blended education before the adoption of the study in blended education through the My School platform and after, in favor of the post-measurement. In light of these results, the study recommended a set of recommendations, including: training students to use modern teaching and learning methods, including blended education, because of its positive impact on developing thinking skills in general and critical thinking skills in particular. It also recommended the need to work on providing the necessary software and applications from In order to activate blended learning and update it periodically, and educate students about the disadvantages of suspicious and non-educational websites. also the study suggested a number of proposals.
Keywords: blended learning; my school platform; critical thinking skills; trends; Corona pandemic (COVID-19)